C3c intrathecal synthesis evaluation in patients with multiple sclerosis Evaluación de la síntesis intratecal de C3c en pacientes con esclerosis múltiple - Bárbara Padilla-Docal; Alberto J Dorta-Contreras; Hermes Fundora-Hernández; Elena Noris-García; Raisa Bu-Coifiu-Fanego; Marlen González-Hernández; Alexis Rodríguez-Rey (Arquivos de Neuro-Psiquiatria)
INTRODUCTION: Multiple sclerosis (MS) is a chronic, inflammatory and progressive disease of the central nervous system in which local inflammatory injuries of the brain white matter appears, being the most outstanding feature the myeline loss (demyelination). OBJECTIVE: To determine if the complement system might be involved in the MS immunopathogeny favouring the mechanism intervening in the myelin destruction. METHOD: Samples of sera and CSF from twelve patients with a diagnosis of MS obtained at the moment of the admission to the hospital at the beginning of the break out, were collected. Levels of C3c and albumin in sera and in CSF were quantified using radial immunodiffusion plates. RESULTS: High values over 80% of intrathecal synthesis were obtained except in one of the patients. CONCLUSION: Intrathecal synthesis of C3c and its liberation to the CSF means that the activation of the complement system in any of the two ways has taken place, and that once performed its biological functions, has suffered a degradation process. INTRODUCCIÓN: La esclerosis múltiple (EM) es una enfermedad crónica, inflamatoria y progresiva del sistema nervioso central que cursa con la aparición de lesiones inflamatorias focales en la sustancia blanca cerebral, en las que lo más llamativo es la pérdida de mielina (desmielinización). OBJETIVO: Conocer si el sistema de complemento puede estar involucrado en la inmunopatogenia de la EM favoreciendo los mecanismos que median la destrucción de la mielina. MÉTODO: Se colectaron muestras de suero y LCR de doce pacientes con diagnóstico de EM obtenidas en el momento del ingreso al inicio del brote. Se cuantificaron los niveles de C3c y albúmina en suero y en LCR en placas de inmunodifusión radial. RESULTADOS: Se obtuvieron altos valores que superan el 80% de síntesis intratecal, menos en uno de los pacientes. CONCLUSION: La síntesis intratecal de C3c y su liberación al LCR significa que ha sucedido la activación del sistema de complemento en alguna de las dos vías y que una vez cumplidas sus funciones biológicas, ha sufrido un proceso de degradación y liberación al LCR en forma de C3c.